The Role of Gakkumdu Bawaslu East Jakarta In Law Enforcement of Election Crimes - Rahmat, Diding; Sujono, Sujono; Sudarto, Sudarto; Farhani, Athari (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2025)
Law enforcement of election crimes is a critical aspect to ensure the creation of a fair, honest, and transparent democratic process. This research discusses the role of the Integrated Law Enforcement Centre (Gakkumdu) under Bawaslu East Jakarta in handling and resolving cases related to election crimes. Gakkumdu Bawaslu East Jakarta is mandated to address various violations, including administrative breaches, code of ethics violations, and criminal acts within the electoral process. This study aims to identify how Gakkumdu East Jakarta carries out its preventive and enforcement functions, as well as to analyse the challenges encountered in implementing these tasks. The research adopts a qualitative method with a literature and legal approach, utilising secondary data sources such as official documents, reports, regulations, and interviews with related stakeholders. The findings reveal that Gakkumdu East Jakarta plays a pivotal role in maintaining electoral integrity by actively monitoring, investigating, and processing election violations. However, several obstacles persist, notably limited human and financial resources, the complexity of legal procedures, and challenges in inter-institutional coordination between Bawaslu, the police, and the prosecutor’s office. This research emphasizes the need for improved institutional synergy, capacity building, and clearer regulatory frameworks to enhance the effectiveness of Gakkumdu’s performance in future elections. Strengthening these aspects is vital to upholding democratic values and ensuring that elections run according to the principles of fairness and justice.